DAMPAK KEBIJAKAN PEMERINTAH TERKAIT SISTEM ZONASI PENDIDIKAN STUDY DI SMAN 1 AIKMEL - Agustini, Baiq Rina (PELITA NUSA TENGGARA, 2024)
Education is a learning process that a person goes through to gain knowledge. Education in Indonesia is not evenly distributed, so the government has issued a zoning system policy. The aim of this research is to determine the impact of implementing the study zoning system policy at SMAN 1 AIKMEL. The approach in this research uses a qualitative approach with a case study type of research. The data sources in this research are interviews and observations. Data analysis uses a 3-stage flow, 1) data condensation, 2) data display, 3) drawing conclusions and results. The results of this research are to determine the negative and positive impacts on school quality and students.